Serum versican as a potential biomarker in patients with uterine fibroids: A study from Eastern India - Pratima Jasti; Suchitra Kumari; Sweta Singh; PP Anudeep (Journal of Family Medicine and Primary Care)
Objective: Versican is a chondroitin sulphate proteoglycan with raised expression at site of inflammation, and uterine fibroids are associated with local inflammation. Hence, this study aimed to estimate serum Versican levels in pre-menopausal women with uterine fibroids to evaluate its diagnostic efficiency. Materials and Methods: This case–control study included forty uterine fibroid cases and 40 healthy controls. Cases clinically evaluated with USG findings, that is number, location of fibroid and volume calculated by prolate ellipse formula a × b × c × 0.523 (a – height, b – width, c – depth). Biochemical investigations, that is serum Versican levels, were estimated by ELISA with total cholesterol, HDLc and LDLc. Triglycerides by fully automated chemistry analysers. Serum biochemical parameters were compared and correlated with volume of fibroid. Area under receiver operating characteristic curve was calculated along with cut-off value to determine diagnostic potential of Versican, differentiating women with fibroids. Results: In the present study, patients with fibroids had decreased levels of serum Versican (79.43 ± 18.60) as compared to healthy controls (101.81 ± 28.24, P < 0.001). There was a statistically significant negative correlation (r = - 0. 307, P = 0.04) between serum Versican level and volume of fibroid. Area under ROC was 0.726 (95% CI: 0.616-0.836; P = 0.001). The best cut-off value for serum Versican level was 96.90 ng/ml with 90% sensitivity and 48% specificity. Conclusion: Serum Versican levels were found significantly lower in women with fibroid with a negative correlation with volume of fibroid uterus. Furthermore, extensive study would help in substantiating diagnostic potential of serum Versican in fibroid uterus patients.